2018
DOI: 10.1016/j.jacc.2018.04.084
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Standard- and Low-Dose Rivaroxaban in Asians With Atrial Fibrillation

Abstract: Compared to standard-dose rivaroxaban, low-dose rivaroxaban in Asian patients with AF was associated with similar risks of thromboembolism and bleeding except myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 28 publications
1
29
1
Order By: Relevance
“…Thus, the current results differ from recent real-world study results, in which reduced-dose NOAC treatment was associated with increased rates of thromboembolic and major haemorrhagic events, along with stroke/SE and myocardial infarction, in Japanese patients with NVAF 18 32. Of note, the proportions of patients initiated on reduced doses of NOACs were higher than those reported in studies conducted in the USA,33–35 Korea and Taiwan36–39 and in real-world studies in Japan 17 18 40. It is likely that the high rates of dose reduction observed in the current study were primarily attributable to the risk characteristics of the patient sample.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, the current results differ from recent real-world study results, in which reduced-dose NOAC treatment was associated with increased rates of thromboembolic and major haemorrhagic events, along with stroke/SE and myocardial infarction, in Japanese patients with NVAF 18 32. Of note, the proportions of patients initiated on reduced doses of NOACs were higher than those reported in studies conducted in the USA,33–35 Korea and Taiwan36–39 and in real-world studies in Japan 17 18 40. It is likely that the high rates of dose reduction observed in the current study were primarily attributable to the risk characteristics of the patient sample.…”
Section: Discussioncontrasting
confidence: 99%
“…However, these studies are still selective, namely regarding patient recruitment, so the extent of inappropriate dosing, in everyday clinical practice, may be underestimated . Another important point is that studies indicated that low‐dose rivaroxaban may be less effective than standard‐dose rivaroxaban without lowering the adverse effect of bleeding . However, this can be explained, in part, by clinicians not always prescribing according to the guidelines, introducing this reduced‐dose regimen in patients who should be receiving the standard dose.…”
Section: Discussionmentioning
confidence: 99%
“…11 Another important point is that studies indicated that low-dose rivaroxaban may be less effective than standard-dose rivaroxaban without lowering the adverse effect of bleeding. 86 However, this can be explained, in part, by clinicians not always prescribing according to the guidelines, introducing this reduced-dose regimen in patients who should be receiving the standard dose. Therefore, these patients become unintentionally undertreated, which increases their risk of thromboembolic complications.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers from Taiwan have published several papers comparing the effectiveness and safety of NOACs and warfarin. 10) 41) Researchers in Korea have also published several studies comparing the effectiveness and safety of NOACs with warfarin. 42) 43) 44) 45) 46) Korean researchers have also analyzed special populations, such as patients with low body-weight and liver disease, which were not included in the pivotal RCTs of NOACs.…”
Section: Cardiovascular Researchers Using the National Health Informamentioning
confidence: 99%